Noninvasive prenatal HPA‐1 typing in HPA‐1a negative pregnancies selected in the Polish PREVFNAIT screening program. Issue 11 (27th September 2018) - Orzińska, Agnieszka; Guz, Katarzyna; Uhrynowska, Małgorzata; Dębska, Marzena; Mikula, Michal; Ostrowski, Jerzy; Ahlen, Maria Therese; Husebekk, Anne; Brojer, Ewa
Abstract : BACKGROUND: Anti‐HPA‐1a alloantibodies in HPA‐1a negative mothers can lead to fetal/neonatal alloimmune thrombocytopenia (FNAIT). Noninvasive prenatal testing (NIPT) of HPA‐1a determines fetuses at risk and the course of maternal antenatal treatment. STUDY DESIGN AND METHODS: The aim was to develop and validate HPA‐1a NIPT by real‐time polymerase chain reaction (PCR) or next‐generation sequencing (NGS) for a high‐throughput screening setting. DNA from 328 plasma samples of 299 HPA‐1a negative pregnant women was examined for HPA‐1a by real‐time PCR and in two cases also by NGS (Ion Torrent). The results were compared with neonatal HPA‐1a genotyping in 281 cases. RESULTS: HPA‐1a NIPT was negative in 44 of 51 HPA‐1a negative fetuses, inconclusive in five, and false positive in two. In 228 of 229 HPA‐1a positive fetuses, the NIPT results were positive (mean threshold cycle 36.0 ± 1.7) and inconclusive in one. In 22 cases with HPA‐1a positive fetuses analyzed twice, the sensitivity of HPA‐1a detection was significantly higher at 28 weeks compared with 16 to 20 weeks. NGS efficiently detected the ITGB3 coding HPA‐1a/b (1% and 5% fetal HPA‐1a reads). CONCLUSION: Real‐time PCR is reliable to predict the fetal HPA‐1a positive genotype in a screening study, but false‐positive results are reported in 4%, with unnecessary prenatal treatment if anti‐HPA‐1a is detected.